Digresiones sobre los diarios de escritores (Charles Du Bos, entre Alejandra Pizarnik y Julio Ramón Ribeyro) - Giordano, Alberto (Universidad Nacional del Litoral, 2010)
One of the ways in which writers exercise the literary criticism in private (a privacy almost always pierced by expectations of the public sphere) is through the writing of their intimate diaries. Following the track of the self-reflexiveness as characteristic gesture of the genre, we try to appreciate, in a particular case, the ways in what writers, directly or indirectly,allude to their own practice of writing a diary when they annotate and comment the impressions that their readings of the another writers diaries have left them. ¿What did Alejandra Pizarnik and Julio Ramón Ribeyro find in Charles Du Bos’diaries, those diaries so close to the form of the essay because they are the diaries of a critic, as so that the report of the consequences of that encounter has filled several entries of their respective diaries? ¿How can we interpellate the Du Bos’s intimate style, his formal elections and his conceptions of the literature and the criticism? Trough a play  of readings interested in recognize similarities and differences, this work suggests answers to these questions entries of their respective diaries? ¿How can we interpellate the Du Bos’s intimate style, his formal elections and his conceptions of the literature and the criticism? Trough a play of readings interested in recognize similarities and differences, this work suggests answers to these questions.